A simple strategy to enhance electrical conductivity of nanotube-conjugate polymer composites via iodine-doping1. Issue 95 (15th October 2015) - Fan, Lina; Xu, Xuecheng
<x xml:space="preserve">Abstract</x> Only the conductivities of iodine-doped CNT–polymer composites containing heteroatoms show a sharp increase.